Carrageenan from Chondracanthus Chamissoi Algae: Extraction process and experimental evaluation as green corrosion inhibitor for P22 steel in HCl - Zavaleta Gutiérrez, N.; Alvarado Loyola, L.; Angelats Silva, L.; Ñique Gutierrez, N.; Duffó, Gustavo Sergio (Russian Association of Corrosion Engineers, 2022)
Fil: Zavaleta Gutiérrez, N.. Universidad Nacional de Trujillo.; Perú